Systemic and local evidence for complement involvement in chronic spontaneous urticaria. Issue 5 (3rd July 2021) - Alizadeh Aghdam, Mehran; van den Elzen, Mignon; van Os‐Medendorp, Harmieke; van Dijk, Marijke R.; Knol, Edward F.; Knulst, André C.; Röckmann, Heike; Otten, Henny G.
Abstract: Background: The pathogenesis of chronic spontaneous urticaria (CSU), including the mechanism of action of omalizumab, remain unclear. We hypothesized complement system involvement given the often fast clinical response induced by treatment, including omalizumab. Therefore, we assessed the role of various complement factors surrounding omalizumab treatment. Methods: Thirty CSU patients (median age 42 [range 21–70]; 73 % female) with a median once daily Urticaria Activity Score over 7 days (UAS7) score at baseline of 31.5 points were enrolled. Treatment consisted of six administrations of 300 mg omalizumab every 4 weeks succeeded by a follow‐up period of 12 weeks. Four punch skin biopsies were taken per patient; at baseline from lesional skin, at baseline from nonlesional skin, and after 1 and 7 days from formerly lesional skin. Complement activity, including C1q, C3, C3bc/C3, C4, C4bc/C4, C5a, and Membrane Attack Complex in peripheral blood were analyzed and complement activation in the skin was determined by the analysis of C4d deposition. Results were related to the clinical response to omalizumab. Results: Fifteen patients showed a UAS7 score of 6 or lower (median 0) at Week 24, 15 patients did not (median 16). Lesional skin biopsies at baseline revealed complement deposition (C4d) in blood vessels in the papillary dermis of 53% (16/30) of the patients, which suggests involvement of immune complexes in the pathogenesis of urticaria. Moreover, indication of increased complement activation in CSU was substantiated by increased C5a levels in peripheral blood compared to healthy controls ( p  = 0.010). The clinical effect of omalizumab could not be linked to the variation of complement components. Conclusions: Both C4d deposition in lesional skin and elevated C5a levels in peripheral blood indicate the involvement of complement activation in the pathogenesis of CSU. No correlation was found between omalizumab and activation of complement indicative of independent processes in the immunopathogenesis of CSU.